2001
DOI: 10.1002/jat.778
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of trichloroethylene following inhalation and drinking contaminated water

Abstract: The neurobehavioural effects of trichloroethylene (TCE) were studied in rats following administration of the solvent orally (350, 700 and 1400 ppm in drinking water for 90 days) and through inhalation (376 ppm for 4 h a day, 5 days per week for 180 days). Various aspects of spontaneous locomotor activity were assessed at different periods after exposure through either of the routes. Oral exposure to TCE had no significant effect on spontaneous locomotor activity or cognitive ability, whereas inhalation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The neurological effects of TCE have long been known, although the pathological correlates have been somewhat controversial in animals and humans (Schaumburg, 2000). More recent data have shown that inhalation of TCE in the rat after 60 days was found to elicit locomotor impairments (Waseem et al, 2001). Additionally, two recent reports have identified links between long-term TCE exposure and PD in humans and described the creation of a TCE animal model of PD.…”
Section: Cannon and Greenamyrementioning
confidence: 99%
“…The neurological effects of TCE have long been known, although the pathological correlates have been somewhat controversial in animals and humans (Schaumburg, 2000). More recent data have shown that inhalation of TCE in the rat after 60 days was found to elicit locomotor impairments (Waseem et al, 2001). Additionally, two recent reports have identified links between long-term TCE exposure and PD in humans and described the creation of a TCE animal model of PD.…”
Section: Cannon and Greenamyrementioning
confidence: 99%
“…Dieldrin ranked second among agricultural chemicals used in the US with a peak in the mid-1960s, with the use of approximately 20 million pounds per year [30]. Recent animal model data show that inhalation of TCE creates motor impairment after 60 days [35]. In addition, studies in animal models have shown that dieldrin exposure replicates many of the neuropathological changes associated with PD [33].…”
Section: Genetic and Environmental Influencesmentioning
confidence: 99%